The Role of Vegetation in the Urban Policies of European Cities in the Age of the Sustainable City - Alexandre, Frédéric (European Spatial Research and Policy, 2014)
The emergence of the modern concept of the sustainable city raises afresh the longstanding issue of the place and role of vegetation in urban and peri-urban areas in Europe. The awareness of biodiversity and the exploration of the services provided by ecosystems both lead to the development of ecological networks based on green spaces in and around the city. The establishment of these networks converges with the control of urban growth and urban sprawl, with the ‘green belts’.Drawing on the development of public policy governing the place of vegetation in Berlin, London and Paris, this article seeks to show the correspondences that have developed in the discussions of urban policy carried on in the major industrialized countries, and also the conflicting goals which these policies are meant to implement.